Guidelines for the registration of assessor, hygiene technician and occupational health doctor (Jabatan Keselamatan dan Kesihatan Pekerjaan Malaysia, 2006)
This guidelines lay down the qualifications for the duties of and the procedure for registration of an assessor, a hygiene technician and an occupational health doctor in pursuance to the requirements of the Occupational Safety and Health (Use and Standard of Exposure Chemical Hazardous to Health) Regulations 2000 [P.U. (A) 131].